The ECU as an investment currency - Swiss Bank Corporation ([Basle] ; Swiss Bank Corporation, 1985)
This booklet is intended mainly for investors and their advisers. It outlines the control mechanisms to which the ECU is subject as a currency basket the types of investment possibilities in ECU issues, and the way those alternatives compare with other forms of investment.
usc 03/08/2017
Loans
Keywords: Capital market; European currency unit; Europe--European Economic Community countries